A new intergovernmental science-policy panel on chemicals, waste and pollution (ISP-CWP)-presenting a conceptual structure for its interdisciplinary expert committee including multidisciplinary civil society scientists - Alexander-White, Camilla; Welton, Tom (Frontiers in Environmental Science, 2025)
This perspectives article explores the inception, structure, functions, and anticipated impacts of the new Intergovernmental Science-Policy Panel on Chemicals, Waste and Pollution (ISP-CWP), established in Punta del Este, Uruguay on 20 June 2025. We look specifically at the role of its prospective Interdisciplinary Expert Committee (IEC) and propose a potential working structure, to ensure that the Panel has access to a sufficient breadth of multidisciplinary expertise. This will be essential to enable the design of a successful and impactful work programme. We discuss how the evidence and knowledge can be focused around three axes: (i) environmental/health impact, (ii) societal service and (iii) readiness of solutions. We look to a future where an inclusive and diverse IEC can make impactful recommendations for innovative policy and technological solutions to prioritised pollution issues.